2015
DOI: 10.18632/oncotarget.2970
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal domain of SMYD3 serves as a unique HSP90-regulated motif in oncogenesis

Abstract: The SMYD3 histone methyl transferase (HMTase) and the nuclear chaperone, HSP90, have been independently implicated as proto-oncogenes in several human malignancies. We show that a degenerate tetratricopeptide repeat (TPR)-like domain encoded in the SMYD3 C-terminal domain (CTD) mediates physical interaction with HSP90. We further demonstrate that the CTD of SMYD3 is essential for its basal HMTase activity and that the TPR-like structure is required for HSP90-enhanced enzyme activity. Loss of SMYD3-HSP90 intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 50 publications
5
69
1
Order By: Relevance
“…The remaining part of the SET (aa94-242) follows the MYND domain and it is formed by an intermediate or linker region (I-SET) and the C-SET domain, which contains key residues for the catalytic activity ( Figure 1). In SMYD3, the TPR-like domain (aa271-428) appears to modulate the association with the MEEVD peptide within HSP90 and likely many other proteins [10,14]. The HSP90 interaction In SMYD3, the TPR-like domain (aa271-428) appears to modulate the association with the MEEVD peptide within HSP90 and likely many other proteins [10,14].…”
Section: Smyd3 Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The remaining part of the SET (aa94-242) follows the MYND domain and it is formed by an intermediate or linker region (I-SET) and the C-SET domain, which contains key residues for the catalytic activity ( Figure 1). In SMYD3, the TPR-like domain (aa271-428) appears to modulate the association with the MEEVD peptide within HSP90 and likely many other proteins [10,14]. The HSP90 interaction In SMYD3, the TPR-like domain (aa271-428) appears to modulate the association with the MEEVD peptide within HSP90 and likely many other proteins [10,14].…”
Section: Smyd3 Structurementioning
confidence: 99%
“…In SMYD3, the TPR-like domain (aa271-428) appears to modulate the association with the MEEVD peptide within HSP90 and likely many other proteins [10,14]. The HSP90 interaction In SMYD3, the TPR-like domain (aa271-428) appears to modulate the association with the MEEVD peptide within HSP90 and likely many other proteins [10,14]. The HSP90 interaction positively regulates SMYD3 in vitro methylation activity, and point mutations in residues that are crucial for HSP90 association affect SMYD3 cellular compartmentalization ( Figure 1) [14].…”
Section: Smyd3 Structurementioning
confidence: 99%
See 1 more Smart Citation
“…SMYD3 in vitro activity can be enhanced by Hsp90 and DNA binding [2,18]. The Hsp90 binding site has been mapped to a TPR-like C-terminal domain (CTD) [19]. Due to the closed conformation, the predicted Hsp90 binding site is half-buried and therefore the question remains how Hsp90 binds to SMYD3 and enhances its activity.…”
Section: Introductionmentioning
confidence: 99%
“…Further potential for therapeutic applications associated with SMYD3 are manifest in the recent findings that a degenerate tetratricopeptide repeat (TPR)-like domain encoded in the SMYD3 Cterminal domain (CTD) mediates physical interaction with the nuclear chaperone, HSP90 23 . In the same study, it is further demonstrated that the CTD of SMYD3 is essential for its basal HMTase activity and that the TPR-like structure facilitates HSP90-enhanced catalysis.…”
Section: Figure 2: Ribbon Structure Of Smyd3mentioning
confidence: 99%